THE GRIEF OF RACHEL WATSON IN THE GIRL ON THE TRAIN FILM - Pambayun, Aulia Putri; Natsir, Muhammad; Asanti, Chris (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
The Girl on The Train Film tells the story of a woman named Rachel. Rachel is the main character in the film that experienced grief in her life. Grief is the sorrow that occurs in life after someone is losing his loved one. The objective of the study is to find out the grief experienced by Rachel in The Girl on The Train Film. The researcher chooses the theory of five stages of grief by Kubler Ross to analysis the data in this study. This study is included in qualitative research because the researcher examines the main character's psychological state by using Kubler Ross theory through the dialogue from the script of the film. The source of the data on this study is The Girl on The Train film and script. From the research findings, it is found that Rachel went through the five stages of grief by Kubler Ross. The stages are denial, anger, bargaining, depression, and acceptance. At first, Rachel did not accept the divorce with her ex-husband. However, in the end of the story, she decided to move on and continue her life.